Willingess to quit smoking and its associated factors among undergraduate student smokers in a Malaysian public university - Junior, Imandojemu Wilson (2017)
Background of study: Tobacco smoking has shown to be the largest preventable cause of death in the world, whereby each day 13000 people die prematurely because of tobacco use and 3 to 6 million people die every year, with current trend of cigarette use, it will cause 8 million deaths annually by 2030 (CDC, 2016). In Malaysia smoking-related diseases are considered important public health issues where they were the main cause of mortality with 10,000 deaths reported annually. This study is aimed at assessing the willingness of young student smokers to quit smoking and the associated factors, which may inform policy makers to devise measures and policies to assist the successful quitting of smokers.